2012
DOI: 10.1080/19393210.2012.705335
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in goat and ovine milk from Calabria (Italy) by ICP-AES

Abstract: There are many sources of contamination to which milk could be exposed: grazing animals can ingest contaminants present in nature, such as lead in soil, or that have been deposited on grass, resulting from industrial emissions. Another possible route of contamination is represented by feed for animals, which may contain heavy and essential metals. The potential of high-resolution inductively coupled plasma spectrometry was evaluated to quantify reliably various toxic and essential elements (Fe, Zn, Pb, Cr, Ni,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 8 publications
0
27
2
Order By: Relevance
“…In our study, Zn concentrations were similar to those previously reported in camel, cow, buffalo, and yak milk (1.24-6.2 mg g À1 ). [22][23][24][25] Our values, however, were lower than the reported in goat milk (11.31 mg g À1 ) by Licata et al The concentration of Al ranged from 0.277 to 0.397 mg g À1 in our study, while Al was not detected in Osorio's study. The concentrations of Cu, Mn, and Mg were in agreement with those reported in the literature.…”
Section: Discussioncontrasting
confidence: 83%
“…In our study, Zn concentrations were similar to those previously reported in camel, cow, buffalo, and yak milk (1.24-6.2 mg g À1 ). [22][23][24][25] Our values, however, were lower than the reported in goat milk (11.31 mg g À1 ) by Licata et al The concentration of Al ranged from 0.277 to 0.397 mg g À1 in our study, while Al was not detected in Osorio's study. The concentrations of Cu, Mn, and Mg were in agreement with those reported in the literature.…”
Section: Discussioncontrasting
confidence: 83%
“…Minerals are considered essential elements. For instance, calcium, copper, and selenium are essential minerals for normal human body functions, as they are involved in many physiological processes (Alasalvara et al, 2002;Licata et al, 2012). However, heavy metals such as lead (Pb), arsenic (As), and cadmium (Cd) may also be found in milk (Swarup et al, 2005;Shailaja et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After cooling, the resulting solutions were evaporated to semidried mass to remove an excess acid, and then diluted up to 50.0 mL in volumetric flasks and kept as a stock sample solution, and were analysed using methodology given by Jalbani N. et al in 2009. (17) …”
Section: Sample Preparationmentioning
confidence: 99%
“…(Caggiano R et al 2005, Tuzen M et al 2008) Cu, Zn and Se are essential metals for normal function of our body, however, from the toxicological point of view, their intake in higher amounts above safe recommended levels may be risky to the human health. (Licata P et al 2012) It is well-known that the Cd and Pb have the greatest injurious effects on renal tissue and nervous system, respectively. (Neal AP and Guilarte TR 2013) Contamination of dairy products with Aluminum may result from the environment, but the concentration of this element increases notably with processing, packaging and food additives.…”
Section: Introductionmentioning
confidence: 99%